Influence of Brand Prestige and Lifestyle on The Purchase Decision (Survey of Starbucks HZ Tasikmalaya Consumers) - Vira Nur Zahra; Budhi Wahyu Fitriadi; Rita Tri Yusnita (Journal of Indonesian Management, 2023)
The purpose of this study was to determine the effect of brand prestige and lifestyle on the purchasing decisions of Starbucks HZ Tasikmalaya consumers. The research method used is a quantitative method with a survey approach to 110 respondents who are consumers of Starbucks HZ Tasikmalaya. The type of data used is primary data. The data analysis technique used is multiple regression analysis. The results of this test prove that brand prestige and lifestyle have a significant effect either partially or simultaneously on purchasing decisions of Starbucks HZ Tasikmalaya consumers